Understanding digital humanities - Berry, David M. (David Michael) (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2012)
"Confronting the digital revolution in academia, this book examines the application of new computational techniques and visualisation technologies in the Arts & Humanities. Uniting differing perspectives, leading and emerging scholars discuss the theoretical and practicalchallenges that computation raises for these disciplines"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Humanities -- Data processing; Digital media; Aufsatzsammlung